Pengaruh Profitabilitas, Kepemilikan Institusional, Kebijakan Deviden, dan Ukuran Perusahaan Terhadap Kebijakan Hutang - Aldi Al Adiat; Hesty Ervianni Zulaecha; Imam Hidayat; Djenny Sasmita (Jurnal Publikasi Ilmu Manajemen, 2022)
This research aims to examine the influence of profitability, institutional ownership, and dividend policy on debt policy on companies from automotive sub-sector manufacturing companies listed on the Indonesia Stock Exchange (IDX). The research period used is 7 years which is the period 2015-2021. The research population includes all automotive sub-sector manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the period 2015-2021. Sampling techniques use purposive sampling techniques. Based on the established criteria obtained 6 samples of companies from automotive sub-sector manufacturing companies. The type of data used is secondary data obtained from the Indonesia Stock Exchange website. The method of analysis used is the regression analysis of the data panel. The result showed the Return On Asset has a significant positive effect on debt policy. Institutional ownership that has no effect on the debt policy. The dividend policy has no effect on the debt policy. Firm size has no effect on the debt policy. Return On Asset, Institutional ownership, and Dividend policis Jointly affect Debt policy.